PPN Jasa Aplikasi Pada Ojek Online (Ojol) - Wijaya, Suparna; Wahyudi, Sugeng (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2021)
The development of technology makes online motorcycle taxis have users and partners that are increasing rapidly every year. However, this also brings problems related to the taxation aspect, namely in determining the business model and the very large number of realtime transactions. The purpose of this study was to determine the treatment of value added tax in an application company and the applicable tax provisions. The method used is descriptive qualitative using literature studies and interviews. The results obtained information that value added tax is imposed on drivers / partners as users of application services provided by online motorcycle taxi operators. The transaction submission of applications carried out by online motorcycle taxi operators does not fulfill the elements of being a retail entrepreneur because there is already a contract between the two parties. So that based on taxation provisions, online motorcycle taxi operators should make a tax invoice for each of these submissions, regardless of whether the application user has an NPWP or not.